Are patients with primary glomerular disease at increased risk of malignancy? - Han, Jialin; Zhao, Yinshan; Canney, Mark; Atiquzzaman, Mohammad; Keown, Paul; Levin, Adeera; Barbour, Sean (Nephrology, dialysis, transplantation, 2024)
ABSTRACT Over the past decade, several observational studies and case series have provided evidence suggesting a connection between glomerular diseases and the development of malignancies, with an estimated risk ranging from 5 to 11%. These malignancies include solid organ tumours as well as haematologic malignancies such as lymphoma and leukaemia. However, these risk estimates are subject to several sources of bias, including unmeasured confounding from inadequate exploration of risk factors, inclusion of glomerular disease cases that were potentially secondary to an underlying malignancy, misclassification of glomerular disease type and ascertainment bias arising from an increased likelihood of physician encounters compared with the general population. Consequently, population-based studies that accurately evaluate the cancer risk in glomerular disease populations are lacking. While it is speculated that long-term use of immunosuppressive medications and glomerular disease activity measured by proteinuria and estimated glomerular filtration rate may be associated with cancer risk in patients with glomerular disease, the independent role of these risk factors remains largely unknown. The presence of these knowledge gaps could lead to a lack of awareness of cancer as a potential chronic complication of glomerular disease, underutilization of routine screening practices in clinical care that allow early diagnosis and treatment of malignancies and underrecognition of modifiable risk factors to decrease the risk of de novo malignancies over time. This review summarizes the current evidence on the risk of cancer in patients with glomerular diseases, explores the limitations of prior studies and discusses methodological challenges and potential solutions for obtaining accurate estimates of cancer risk and identifying modifiable risk factors unique to GN populations. Video 10.1093/ndt/gfad261 Video Watch the video of this contribution at https://academic.oup.com/ndt/pages/author_videos gfad261Media1 6344835995112